Patterns and duration of primary and recurrent treatment in ovarian cancer patients with germline BRCA mutations - Soledad Jorge; Elizabeth M. Swisher; Barbara M. Norquist; Kathryn P. Pennington; Heidi J. Gray; Renata R. Urban; Rochelle L. Garcia; Kemi M. Doll (Gynecologic Oncology Reports, 2019)
The objectives of this study were to describe the patterns and duration of primary and recurrent treatment in patients with ovarian cancer (OC) harboring germline BRCA1 and BRCA2 (BRCA) mutations. A retrospective review of BRCA mutation carriers with advanced, high-grade OC diagnosed between 2004 and 2014 with at least 3 years of follow-up (or until death) was undertaken. Descriptive statistics were calculated and a Swimmer's Plot used to depict disease course. Forty BRCA mutation carriers (26 BRCA1, 14 BRCA2) were identified. Mean age was 54 (range 32–77). All had cytoreductive surgery and received platinum chemotherapy. Median platinum-free interval was 11.9 months (IQR 3.6–21.9). Among 28 patients who recurred, median number of treatment lines was 4 (IQR 3–6), with a median of 2 (IQR 2–3) platinum lines. On average, patients who recurred spent 32% (IQR 20–43%) of their time after diagnosis receiving cytotoxic chemotherapy and 54% (IQR 42–67%) of the time on some cancer-directed therapy, including maintenance. Median overall survival was 79.1 months from diagnosis and 25.4 months after first recurrence. In conclusion, beyond first-line therapy, there was treatment and outcome heterogeneity for BRCA-mutated OC. After OC diagnosis, patients spent close to half their life on treatment. Keywords: Ovarian cancer, BRCA1 and BRCA2 mutations, Disease course, Treatment, Long-term